198. Dosimetric comparison of 3D-Conformal Radiotherapy versus RapidArc for adjuvant treatment of advanced gastric cancer: IRCCS Giovanni Paolo II case study. (December 2018) - Massafra, R.; Nardone, A.; Tamborra, P.; Carbonara, R.; Lioce, M.; Pascali, A.; Didonna, V.
Abstract : Purpose: To implement RapidArc technique with daily IGRT for the adjuvant treatment of advanced gastric cancer in order to achieve good target coverage and useful dose-sparing for organs at risk (OARs) compared to a typical 3D-CRT plan and according to literature[1] . Methods: In June 2017 we compared two different treatment plans for the adjuvant radiotherapy of an advanced gastric adenocarcinoma occurred in a 69 years old female patient: the first one was a 3D-CRT plan with 4 oblique fields in order to improve dose-sparing for kidneys; the second was a RapidArc plan with two coplanar arches. Prescription dose was 45 Gy (1.8 Gy/day) to resected tumor bed, anastomoses and regional lymph nodes. We evaluated dosimetric parameters related to PTV: V95% isodose, D98, D95, D50 and D2 values, Conformity Index (CI), Homogeneity Index (HI). Respect of constraints for OARs (liver, kidneys, colon, spinal cord, heart, lungs) was also considered. Results: PTV Mean Volume was 631, 8 cc. V95% isodose calculated for RapidArc was 785, 8 cc, 1173 cc for 3D-CRT. D98, D95, D50, D2 values were comparable in both plans (44, 1 Gy, 42, 7 Gy, 45 Gy, 46 Gy, respectively). CI and HI of RapidArc plan were better than 3D-CRT plan (CI:1, 24 vs 1, 86; HI:1, 04 vs 1, 08). A better dose-sparing for OARs was obtained with RapidArc (Table 1 ). Monitor Units were 37 + 73 + 65 + 38 for the four beams ofi 3D-CRT plan, 193 for Arc1 and 217 for Arc2 of RapidArc plan. Conclusions: RapidArc allows to achieve a good target coverage with high conformation to PTV and optimal dose-sparing for OARs. This technique should be supported by daily IGRT (with Cone Beam-Computed Tomography or kV/MV) in order to represent a feasible alternative to 3D-CRT for irradiation of upper abdomen that is affected by diaphragmatic excursion; IGRT also reduces inter fraction variability. RapidArc ensures shorter delivery treatment times reducing intra fraction patient and organ motion.